Techno-economic and sustainable energy solution for small industrial estate of Gujranwala, Pakistan-using hybrid microgrid - Amir Ali Shah; Muhammad Mateen Afzal Awan; Ayaz Ahmed Hoshu; Ghulam Hussain Chandio (Mehran University Research Journal of Engineering and Technology)
This research comprises the energy solutions for small industrial estate Gujranwala, Pakistan using HOMER pro simulation software and considering the best possible energy plan with maximum reliability, cost-effectiveness, efficiency and availability. Small industrial estate is an industrial zone comprising small industrial units (ceramics, cutlery, sports goods, surgical instruments, tough tile, garments, etc.) up to a maximum energy consumption of 500KW each, organized by provincial government of Punjab, Pakistan. In this research, we have presented an optimized hybrid microgrid framework to ensure a consistent and reliable energy supply for the small industrial estate of Gujranwala, Punjab, Pakistan. In this research work, we have collected the required data related to the availability of natural energy resources in the Gujranwala region like solar DNI (direct normal radiations), GHI (global horizontal irradiations) wind speed and temperature from NREL official website. Then We have estimated the maximum power demand by collecting real-time one-year data from the existing 132kv Shaheenabad grid, Punjab, Pakistan, which is feeding electric power to an existing small industrial state Gujranwala similar to a new industrial estate under construction. We have proposed an optimized hybrid microgrid design by integrating that collected data into HOMER Pro simulation application including electrical load profiles, solar irradiance data, regional temperature profile, diesel costs, PV module longevity, degradation rates, efficiency, costs of PV modules, national grid energy pricing and net metering with national grid. A comprehensive assessment of the proposed optimal system involves technical and economic long-term benefits for small industrial estate Gujranwala, Pakistan.